2000
DOI: 10.1023/a:1005463020252
|View full text |Cite
|
Sign up to set email alerts
|

Selecting foils for identification lineups: Matching suspects or descriptions?

Abstract: Two experiments directly compare two methods of selecting foils for identification lineups. The suspect-matched method selects foils based on their match to the suspect, whereas the description-matched method selects foils based on their match to the witness's description of the perpetrator. Theoretical analyses and previous results predict an advantage for description-matched lineups both in terms of correctly identifying the perpetrator and minimizing false identification of innocent suspects. The advantage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
98
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(107 citation statements)
references
References 18 publications
7
98
2
Order By: Relevance
“…The faces in the mugbook were selected in the same way as the faces in the lineup. We used a combination of the match-to-target and match-to-description strategies (see Tunnicliff & Clark, 2000, for a review of foil selection procedures). The mugbook and lineup foils were selected from a larger pool of about 40 faces on the basis of their similarity ratings to the target photographs.…”
Section: Methodsmentioning
confidence: 99%
“…The faces in the mugbook were selected in the same way as the faces in the lineup. We used a combination of the match-to-target and match-to-description strategies (see Tunnicliff & Clark, 2000, for a review of foil selection procedures). The mugbook and lineup foils were selected from a larger pool of about 40 faces on the basis of their similarity ratings to the target photographs.…”
Section: Methodsmentioning
confidence: 99%
“…On the one hand, it might be argued that selecting the fillers based on their physical match to the suspect's emotional appearance may reduce the hit rate, because lineup member matching emotional expression will increase the physical similarity of 27 EMOTIONAL APPEARANCE the lineup members (see Luus & Wells, 1991). However, results are inconsistent across experiments (see Tunnicliff & Clark, 2000 for a review), with some showing higher hit rates for description-matched compared to suspect-matched lineups (Lindsay, Martin, & Webber, 1994;Luus & Wells, 1991) and others not finding any difference between the two filler selection strategies (Tunnicliff & Clark, 2000). The results for false alarms are also conflicting, with some finding no difference across strategies (Luus & Wells, 1991), and others finding that false alarm rates tend to be larger in description matched compared to suspect matched lineups (Lindsay et al, 1994;Tunnicliff & Clark, 2000).…”
Section: Applied Implicationsmentioning
confidence: 99%
“…Specifically, the similarity of the foils to the perpetrator in a target-absent lineup is mediated by the similarity of the innocent suspect to the perpetrator in such a way that the foils cannot (on average) be more similar to the perpetrator than is the innocent suspect, making the innocent suspect the person in the lineup who is most likely to be identified. Tunnicliff and Clark (2000) suggested that description-matched foil selection should reduce (or possibility eliminate) the backfire effect as well. have recently reported a metaanalysis of four studies in which suspect-matched and description-matched lineups were compared directly.…”
Section: Foil Selection: Suspect Matched Versus Description Matchedmentioning
confidence: 99%
“…The question is illustrated in Table 2 with data from a typical eyewitness identification experiment (Tunnicliff & Clark, 2000). In this experiment, participants were witnesses to a staged crime: A perpetrator (a paid actor) came to the laboratory and stole an envelope full of cash.…”
mentioning
confidence: 99%